A Behavioral Understanding of Investment Horizon and Firm Performance - Souder, David; Reilly, Greg; Bromiley, Philip; Mitchell, Scott (Organization Science, 2016)
Observers have argued that firms overly emphasize short-term results at the expense of long-run value. Using a behavioral perspective, we analyze three hypotheses related to this general argument. First, we examine the association of investment time horizons with firm performance, contributing new theory that argues for a quadratic rather than linear association. Second, because the tendency toward immediate results could reflect stock market pressures, we consider how the interaction of investor patience and firm horizon relates to firm performance. Third, we examine the argument’s implication that most firms have investment horizons at a level where marginal increases in horizon associate positively with firm performance. Measuring horizon as the expected useful lives of capital expenditures, we find empirical support for the hypothesized quadratic relation in a large-scale, multiyear sample of U.S. publicly held manufacturing firms and confirm that a majority of firms have horizons in the region where our models predict increases in horizon positively influence performance. We also find that the most positive returns occur when long horizon investments are aligned with investor patience.